The Role of the Logistic Potential of a Health Resort on Building Tourism Potential : a Case Study of the Cieplice Resort (Uzdrowisko Cieplice) - Beata Mucha (Studia Periegetica, 2016)
"Uzdrowisko Cieplice" [the Cieplice Resort] is one of the oldest health resorts in Poland, which owes its popularity to its healing thermal springs. The Cieplice Baths constitute a modern water-recreation centre and complement the resort's wellness package. The development of logistical services is stimulating a growing need for heath-resort services, including recreation and leisure services. Its convenient location near mountain resorts equipped with an infrastructure for winter sports (including downhill and cross-country skiing), is an additional advantage of the town's location. The aim of this article is to describe the Cieplice Resort and highlight its logistic infrastructure, including its facilities, cycle paths, and tourist trails, which allow the resort's visitors, who come here to see the sights and relax, to do so actively all the year round. For the purpose of their research, the author's used the method of critically analysing literature and the information published on the Cieplice Resort website. An empirical (initial) study of the logistic infrastructure was complemented with photographs. The Conclusions: A well-developed logistics infrastructure contributes to the competitiveness of a health resort.(original abstract)